Zero-Error Capacity of Duplication Channels - Kovacevic, Mladen (IEEE transactions on communications, 2019)
This paper is concerned with the problem of error-free communication over the i.i.d. duplication channel which acts on a transmitted sequence x 1 · · · x n by inserting a random number of copies of each symbol x next to the original symbol. The random variables representing the numbers of inserted copies at each position i are independent and take values in {0, 1, . . . , r}, where r is a fixed parameter. A more general model in which blocks of ℓ consecutive symbols are being duplicated, and which is inspired by DNA-based data storage systems wherein the stored molecules are subject to tandem-duplication mutations, is also analyzed. A construction of optimal codes correcting all patterns of errors of this type is described, and the zero-error capacity of the duplication channel-the largest rate at which information can be transmitted through it in an error-free manner-is determined for each ℓ and r.